(untitled) (Filološke pripombe, 2019)
The theatrum mundi topos, i.e. seeing the world as a stage, and an individual as an actor on that stage derives from Plato. The Latin metaphor of theatrum mundi, established in the Middle Ages, has constantly been enriched with new meanings. The paper deals with the use of the theatrum mundi topos in Ivo Bresan’s novels, Birds of Heaven (1990) and The Confessions of a Characterless Man (1996). The protagonists of both novels see the world as a stage on which, according to their needs and when forced by their instinct for survival, they take different life roles. Bresan explicitly calls his protagonists actors, for whom the whole world is merely a stage. The theatrum mundi topos is powerfully present in both novels, ranging from understanding of the scholar John of Salisbury, through the baroque understanding of topos to the topos in symbolical works and impossibility of determining identity in permanently changing world, following Pirandello. Due to the use of meaningfully rich topos theatrum mundi, Bresan’s novels become semantically more complex and require an experienced reader.